2017
DOI: 10.1001/jama.2017.9478
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Improvisational Music Therapy vs Enhanced Standard Care on Symptom Severity Among Children With Autism Spectrum Disorder

Abstract: isrctn.org Identifier: ISRCTN78923965.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 33 publications
2
108
1
9
Order By: Relevance
“…51 Em um estudo comparativo entre a aplicação da musicoterapia de improvisação e os cuidados habituais com portadores de TEA, a exemplo de aconselhamento com os pais, observou-se que ambos cuidados promoveram redução nos valores observados no Protocolo de Observação para Diagnóstico de Autismo (PODA), mais especificamente no item "domínio de afeto social". 52 O PODA é um protocolo que tem o escopo de realizar o diagnóstico do autismo, em base às competências sociais e de comunicação observados pelo experimentador na interação de atividades dirigidas. 53 …”
Section: Discussionunclassified
“…51 Em um estudo comparativo entre a aplicação da musicoterapia de improvisação e os cuidados habituais com portadores de TEA, a exemplo de aconselhamento com os pais, observou-se que ambos cuidados promoveram redução nos valores observados no Protocolo de Observação para Diagnóstico de Autismo (PODA), mais especificamente no item "domínio de afeto social". 52 O PODA é um protocolo que tem o escopo de realizar o diagnóstico do autismo, em base às competências sociais e de comunicação observados pelo experimentador na interação de atividades dirigidas. 53 …”
Section: Discussionunclassified
“…BOSCC scores significantly decreased (–2.53, P < 0.05, d = 0.26), but ADOS social affect scores did not (–0.29, P > 0.05, d = 0.15). The fact that the intervention of Bieleninik et al . did not meet their MCID may therefore reflect a problem not with the intervention but with the outcome measure.…”
Section: Engaging Clinical Intuitionmentioning
confidence: 99%
“…Cognizant of the critical need for outcome measures that are sensitive to improvement in social communication, a novel instrument, the Brief Observation of Social Communication Change (BOSCC), was developed. The BOSCC is appropriate for children with minimal spontaneous language (appropriate for the ADOS modules employed by Bieleninik) and can be used to score a 10‐min free‐play interaction. Two intervention studies, not employing music‐based treatments, highlight the BOSCC's sensitivity to change.…”
Section: Engaging Clinical Intuitionmentioning
confidence: 99%
“…Reflecting on my own learning process over a number of RCTs, I find that my earliest trials were often somewhat unclear in their reporting of negative or unexpected results. Our most recent RCT (Bieleninik et al, 2017) taught me that a clearly and unambiguously reported negative resultwhich was admittedly achieved after hard discussions with editors, even over single words in the abstractcan be more helpful than a muddled conclusion that attempts to hide the actual findings. In other words: "Clinical trials is how we learn.…”
Section: Randomised Controlled Trials: Why the Small Print Mattersmentioning
confidence: 99%